Characterization of small plasmids carrying florfenicol resistance gene floR in Actinobacillus pleuropneumoniae and Pasteurella multocida isolates from swine in China - Yao, Xiaohui; Song, Qiangqiang; Zhu, Wei; Wei, Jianchao; Shao, Donghua; Liu, Ke; Li, Zongjie; Qiu, Yafeng; Ma, Zhiyong; Xia, Lining; Li, Beibei (Frontiers in Veterinary Science, 2023)
Actinobacillus pleuropneumoniae and Pasteurella multocida are two important bacterial pathogens in swine industry. In the present study, resistance profiles of nine commonly used antibiotics of A. pleuropneumoniae and P. multocida isolates of swine origin from different regions of China were investigated by determination of minimum inhibitory concentrations (MICs). In addition, genetic relationship of the florfenicol-resistant A. pleuropneumoniae and P. multocida isolates was determined by pulsed-field gel electrophoresis (PFGE). The genetic basis of florfenicol resistance in these isolates were explored by floR detection and whole genome sequencing. High resistance rates (>25%) of florfenicol, tetracycline and trimethoprim- sulfamethoxazole were observed for both bacteria. No ceftiofur- and tiamulin- resistant isolates were detected. Furthermore, all the 17 florfenicol-resistant isolates (nine for A. pleuropneumoniae and eight for P. multocida) were positive for floR gene. The presence of similar PFGE types in these isolates suggested that clonal expansion of some floR-producing strains occurred in the pig farms from same regions. WGS and PCR screening showed that three plasmids, named pFA11, pMAF5, and pMAF6, were the cargos of the floR genes in the 17 isolates. Plasmid pFA11 exhibited novel structure and carried several resistance genes, including floR, sul2, aacC2d, strA, strB, and blaROB − 1. Plasmids pMAF5 and pMAF6 were presented in A. pleuropneumoniae and P. multocida isolates from different regions, suggesting horizontal transfer of the two plasmids are important for the floR dissemination in these Pasteurellaceae pathogens. Further studies of florfenicol resistance and its transfer vectors in Pasteurellaceae bacteria of veterinary origin are warranted.